Sanitary conditions and devices in the apartments XIX-century płocczans on the example of the Jewish quarter and flats in Płock watchman - Milewska, Marta (In the Mirror of Things, 2022)
The nineteenth century favored the appearance of a new sanitary devices. Unfortunately, these inventions were delivered to Polish soil with a long delay, including the inhabitants of the provincial city of Płock. The article is therefore an attempt to present the sanitary condition of flats in Płock in the second half of the nineteenth century, using the example of a watchman in the Jewish district and Płock flats. The aim of the article is to draw attention to the relationship between the sanitary condition of apartments and the health of the city’s inhabitants. The analysis of the housing equipment, their size, distribution and population density allowed to outline the almost catastrophic hygienic conditions in the apartments of the above-mentioned social groups. The sad picture of the hygienic conditions in the apartments in the Jewish district and in the apartments of Płock guards was complemented by the lack of access to running water and improper sanitation. The above omissions allowed to establish that the apartments of the Jewish population in Płock and the Płock watchmen were deprived of basic sanitary facilities, which favored the spread of epidemic diseases.